Continued Compliance and Degree of Satisfaction in Nulligravida and Parous Women with Intrauterine Contraceptive Devices - Adriana Scavuzzi; Alex Sandro Rolland Souza; Melania Maria Ramos Amorim (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2016)
Purpose To evaluate the compliance and degree of satisfaction of nulligravida (has not given birth) and parous (had already given birth) women who are using intrauterine devices (IUDs). Methods A cross-sectional cohort study was conducted comparing nulligravida and parous women who had had an IUD inserted between July 2009 and November 2011. A total of 84 nulligravida women and 73 parous women were included. Interviews were conducted with women who agreed to participate through telephone contact. Statistical analysis was performed with Student s t-test and Mann-Whitney test for numeric variables; Pearson s chi-square test to test associations; and, whenever pertinent, Fisher s exact test for categorical variables. A survival curve was constructed to estimate the likelihood of each woman continuing the use of the IUD. A significance level of 5% was established. Results When compared with parous women, nulligravida women had a higher education level (median: 12 vs. 10 years). No statistically significant differences were found between the nulligravida and parous women with respect to information on the use of the IUD, prior use of other contraceptive methods, the reason for having chosen the IUD as the current contraceptive method, reasons for discontinuing the use and adverse effects, compliance, and degree of satisfaction. The two groups did not show any difference in terms of continued use of the IUD (p = 0.4). Conclusion There was no difference in compliance or the degree of satisfaction or continued use of IUDs between nulligravida and parous women, suggesting that IUD use may be recommended for women who have never been pregnant.